Urgensitas Pendidikan Fiqih dalam Membangun Kesetaraan dan Perdamaian Perspektif Al-Quran - Muslimin, Muslimin; Trisnawati, Rinda; Samsudi, Wedi; Mahtum, Rohiqi; Heryandi, M Tubi (Edukais : Jurnal Pemikiran Keislaman, 2023)
The purpose of this study is to discuss the urgency of fiqh education in building equality and peace in the perspective of the Koran. With the hope that when these aspects have been discussed it can become a shared lesson so that they are more active in spreading peace in a wider scope, not only for certain groups but also for the general public. The research method used is in the form of a literature review while the references used consist of various classic books related to the topic of discussion, such as classic fiqh books, contemporary fiqh, Usul Fiqh, Maqasih Al-Syariah and Tafsir. Meanwhile, the results of this study found that there was a strong influence on 3 aspects of fiqh education in instilling the character of peace, namely aspects of fiqh worship, fiqh muamalah, and fiqh munakahah. These three aspects each have their own principles in forming equality and peace according to the Qur'an. In addition, the principles of gender, social and educational equality were found.